Analisis penerapan tax planning dengan menggunakan metode gross up sebagai efisiensi pajak penghasilan badan pada Koperasi Pegawai Telkom - Azhar, Shofwan; Seftiansyah, Muhammad Dery; Sugito Putra, Toufiq Agung Pratomo (Fair Value: Jurnal Ilmiah Akuntansi dan Keuangan, 2022)
Taxes are viewed from two different sides. Companies, taxes are a burden for use they can reduce company profits, but from a government perspective, taxes are a source of revenue to finance state and regional expenditures. Cooperatives are one of the business entities that are obliged to pay taxes, but paying taxes can reduce the remaining business results of cooperatives and cooperative members. This study aims to calculate how much cooperatives can make tax payments efficient so that cooperatives and members can produce optimal remaining operating results. The research method used is a comparative descriptive method. Based on the results of the study, with the implementation of tax planning , KOPEGTEL can streamline income taxes that previously paid corporate income tax of Rp. 282,449,504, but after-tax planning , KOPEGTEL can pay corporate income tax of Rp. 166,309,116. In addition,after-tax planning , KOPEGTEL can optimize the SHU produced by cooperatives of Rp. 117,565,140, ​​so that it can be interpreted that by doing tax planning , KOPEGTEL can be more efficient in the income tax burden of taxes payable, to increase the remaining results of cooperative operations.